DEVELOPMENT OF ENCAPSULATED DNA VACCINE ENCODING VP6 GENE FROM ROTAVIRUS RV4 IN CHITOSAN NANOPARTICLES AS MEDIATOR FOR INTERNALIZATION INTO MAMMALIAN CELLS - Sanawati, Anna
Rotavirus is a common cause of gastroenteritis in infants and children under five years old. Rotavirus causes approximately 200,000 deaths in children worldwide each year. Two live attenuated rotavirus vaccines have been produced and recommended by WHO for use in routine immunization programs. Although both live attenuated vaccines are promising, but vaccine development is still needed to provide a better and safer rotavirus vaccine. DNA vaccine is a new generation vaccine that is promising to be developed. Among rotavirus structural proteins, VP6 protein can be used in DNA vaccine development because it has immunogenicity and has several conserved epitopes in group A rotavirus, which can provide heterotypic protection. To increase the immune responses against rotaviruses, DNA vaccines should be targeted to the MALT (mucosa-associated lymphoid tissue). In this research, we developed DNA vaccine encoding VP6 protein from human rotavirus strain RV4 that could induce immune responses. DNA vaccine was encapsulated by chitosan nanoparticles so could be administered orally. Construction of VP6 DNA vaccine was conducted by inserting VP6 gene into pVAX1 expression vector to produce pVAX1-VP6. Recombinant plasmid pVAX1-VP6 was characterized and verified by PCR and sequencing. In silico analysis of VP6 epitopes was performed to analyze the peptide fragments that could bind to the MHC I and MHC II. Expression assay of pVAX1-VP6 was conducted in Vero cell line to examine whether the plasmid could be expressed in mammalian cells. pVAX1-VP6 was encapsulated by chitosan nanoparticles and characterized to analyze the size of the particle, zeta potential, entrapment efficiency, morphology, and the internalization and expression ability in Vero cell line. Sequencing analysis was showed that VP6 gene from HRV RV4 gene was 98% homologous with VP6 gene from HRV G1P[8] (GenBank no. JN258858.1), whereas VP6 protein from HRV RV4 was 99% homologous with VP6 protein from HRV G1P[8] (GenBank no. AEK69541.1). Based on amino acid alignment result between VP6 HRV RV4 and VP6 HRV G1P[8], three point mutations (T246I, H316Y and I385V) were found. These mutations did not affect 3D structure of iv VP6 protein. In silico epitope analysis showed that VP6 protein contains conserved epitopes that could bind to MHC I and MHC II, and also potentially induces heterotypic protection. Three point mutations which is located in the epitope area could affected the immunogenicity of the VP6 protein. In silico analysis showed that the T246I mutation significantly increased the binding probability of epitope to the MHC molecules better than the other two mutations. The increasing of binding probability was affected by the hydrophobic interactions between Ile246 from VP6 with Val67 from HLA-A*11:01. The data showed that pVAX1-VP6 was expressed by Vero cells from 24 hour up to 120 hours post-transfection, but the expression started to decrease after 96 hours post-transfection. pVAX1-VP6 was succeeded to be encapsuled by chitosan nanoparticles (NP-pVAX1-VP6) with entrapment efficiency more than 99%. This nanoparticles were spheric, 200 nm in size, and has positive charged. The enzymatic analysis result showed that chitosan encapsulation could protect pVAX1-VP6 from nuclease (Dnase I) degradation. TEM and immunofluoeresence assay results showed that the NP - pVAX1-VP6 could be internalized and expressed by Vero cell line. The immunofluoresence data showed that VP6 protein was located in cytoplasm indicating this antigen can be processed and presented by MHC I and MHC II which induce the cellular and humoral immune responses. This research showed that rotavirus VP6 DNA vaccine is potential to induce cellular and humoral immune responses and it could be administered orally because encapsulated by chitosan nanoparticles.